A Subclass of Janowski Starlike Functions Involving Mathieu-Type Series - Liu, Dong; Araci, Serkan; Khan, Bilal; Aracı, Serkan (MDPI)
To date, many interesting subclasses of analytic functions involving symmetrical points and other well celebrated domains have been investigated and studied. The aim of our present investigation is to make use of certain Janowski functions and a Mathieu-type series to define a new subclass of analytic (or invariant) functions. Our defined function class is symmetric under rotation. Some useful results like Fekete-Szego functional, a number of sufficient conditions, radius problems, and results related to partial sums are derived.
Keywords: Mathieu-type series; Janowski function; starlike function; analytic functions